Growth-promoting characteristics of potential nitrogen-fixing bacteria in the root of an invasive plant Ageratina adenophora - Fang,Kai; Bao,Zhu-Shou-Neng; Chen,Lin; Zhou,Jie; Yang,Zhi-Ping; Dong,Xing-Fan; Zhang,Han-Bo (PeerJ, 2019)
Root endophytic nitrogen-fixing bacteria (reNFB) have been proposed as important contributors to the invasiveness of exotic legumes; however, the reNFB of invasive nonlegumes has received less attention. In particular, the growth-promoting effect of reNFB on invasive plants remains unknown. In this study, 131 strains of potential nitrogen-fixing bacteria were isolated and purified from the roots of the invasive plant, Ageratina adenophora, in Southwest China. Phylogenetically, these reNFB were categorized into three phyla at 97% sequence identity that included Proteobacteria (92.4%), Actinobacteria (4.6%), and Firmicutes (3.1%). The dominant isolates ranked by number were Pseudomonas (80 isolates, 61.1%), Rhizobium (12 isolates, 9.2%), and Duganella (11 isolates, 8.4%). The community composition and diversity of A. adenophora reNFB were markedly different across study regions. The capacity of these reNFB to accumulate indolyl-3-acetic acid (IAA), solubilize phosphate, and produce siderophores was determined. All 131 isolates of reNFB accumulated IAA, 67 isolates solubilized phosphate, and 108 isolates produced siderophores. Among the three dominant genera of reNFB, Pseudomonas had the highest phosphorus solubilization and siderophore production, while the accumulation of IAA in the genus Duganella was the lowest. Interestingly, the calculated reNFB Shannon diversity index of each A. adenophora individual was negatively correlated with the capacity of reNFB to produce growth-promoting products. Six randomly selected isolates from three dominant genera were further used to conduct inoculation experiments, and all isolates showed significant positive growth-promoting effects on A. adenophora seedlings. The contribution of reNFB to the root biomass was higher than that to the shoot biomass. Our results suggest that reNFB, similar to soil or nodular nitrogen-fixing bacteria, can potentially promote plant growth and may play an important role in the invasion of nonleguminous plants. More detailed studies on the correlation between reNFB and invasive plants are necessary.
Keywords: Phosphate solubility; Siderophore production; Inoculation experiment; IAA accumulation; Ageratina adenophora; Root endophytic bacteria